DEEP STRUCTURE AND SOURCES OF MAGNETIC ANOMALIES IN THE SOUTH TATAR BASIN (TATAR STRAIT, JAPANESE SEA) - Proshkina, Z.N.; Valitov, M.G.; Sigeev, I.A. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2024)
The results of structural-density modeling along the profile crossing structures in the southern part of the South Tatar basin located in the Tatar Strait in the north of the Sea of Japan are presented. The purpose of the modeling was to study the deep structure of the area and compare it with the structure of the previously studied central part of the basin. The depths of the upper and lower edges of the magnetized objects were calculated using the tangent method. The structural-density section of the Earth's crust demonstrates the block structure of the basement and, possibly, its differentiation by composition. Calculation of the depth of the edges of magnetically active bodies showed their confinement to the upper crust, mainly to fault zones and volcanic structures. In the central part of the section, altered continental crust with signs of basification was revealed.